OVARIAN RESERVE IN PRETERM GIRLS AT BIRTH AND IN PUBERTY - NATALIA V. Artymuk; SVETLANA I. Yelgina; ELENA N. Nikulina (Фундаментальная и клиническая медицина)
Aim. To estimate the ovarian reserve in preterm girls at birth and in puberty. Materials and Methods. We recruited 100 either preterm or full-term infant girls and 200 adolescent (15-16 years of age) girls born either preterm or full-term (n = 100 per each group) following clinical and ultrasound examination. Results. The levels of pituitary hormones in preterm newborn and adolescent girls were higher while the levels of ovarian hormones were lower compared to those born full-term. Furthermore, both average ovarian volume and average antral follicles count were lower in preterm newborn and adolescent girls in comparison with those born full-term. Conclusion. Ovarian reserve in preterm girls is lower compared to those born full-term and remains depleted at least until the puberty.